2004
DOI: 10.2118/88986-pa
|View full text |Cite
|
Sign up to set email alerts
|

Shaybah-220: A Maximum-Reservoir-Contact (MRC) Well and Its Implications for Developing Tight-Facies Reservoirs

Abstract: Summary This paper presents drilling, completion, well-performance, and reservoir-characterization results of a recently drilled maximum-reservoir-contact (MRC) well in the Shaybah field with a total of eight laterals and an aggregate reservoir contact of 12.3 km (7.6 miles). The well was drilled as part of a pilot program to evaluate both the practical challenges and the reservoir performance impact of MRC wells. The results to date on eight MRC wells in Shaybah indicate signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Economic studies on Shaybah field in Saudi Arabia (a distinctive example for smart wells), showed a four-fold reduction in unit development cost for such completions. Moreover, production testing indicated five-fold increase in productivity index compared to horizontal wells completed in similar facies (Saleri et al, 2003). Several other studies have shown superiority of nonconventional wells when compared to conventional ones in terms of extended reservoir contact length and drainage area, increasing net worth of drilling investment, reducing operational drawdown pressure, and reducing producing gas-oil ratio (Horn et al, 1997;Taylor et al, 1997).…”
Section: Introductionmentioning
confidence: 91%
“…Economic studies on Shaybah field in Saudi Arabia (a distinctive example for smart wells), showed a four-fold reduction in unit development cost for such completions. Moreover, production testing indicated five-fold increase in productivity index compared to horizontal wells completed in similar facies (Saleri et al, 2003). Several other studies have shown superiority of nonconventional wells when compared to conventional ones in terms of extended reservoir contact length and drainage area, increasing net worth of drilling investment, reducing operational drawdown pressure, and reducing producing gas-oil ratio (Horn et al, 1997;Taylor et al, 1997).…”
Section: Introductionmentioning
confidence: 91%
“…The oil column in this reservoir is overlaid by a huge gas cap and is underlain by a weak aquifer. Gravity drainage mechanism with gas cap expansion is the main drive mechanism (Saleri et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In early 2002, the first MRC well was drilled with total reservoir contact of 8.5 km with open hole completion. Drilling and production performance were presented in various SPE papers [Dossary, 2003, Saleri, 2004.…”
Section: Introductionmentioning
confidence: 99%